2015
DOI: 10.1101/gad.254151.114
|View full text |Cite
|
Sign up to set email alerts
|

A genome-scale in vivo loss-of-function screen identifies Phf6 as a lineage-specific regulator of leukemia cell growth

Abstract: We performed a genome-scale shRNA screen for modulators of B-cell leukemia progression in vivo. Results from this work revealed dramatic distinctions between the relative effects of shRNAs on the growth of tumor cells in culture versus in their native microenvironment. Specifically, we identified many “context-specific” regulators of leukemia development. These included the gene encoding the zinc finger protein Phf6. While inactivating mutations in PHF6 are commonly observed in human myeloid and T-cell maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 37 publications
(36 reference statements)
4
81
1
Order By: Relevance
“…Inactivating mutations in PHF6 were subsequently identified in human leukemia of the T and myeloid lineages, highlighting its role as a tumor suppressor gene in these malignancies (Van Vlierberghe et al 2010, 2011. Our group recently described a tumor-promoting role for Phf6 in a murine model of BCR-ABL1 + B-ALL (Williams et al 2006;Meacham et al 2015). In this study, we found that hairpin-mediated knockdown of Phf6 leads to impaired growth of B-ALL cells in vivo.…”
mentioning
confidence: 54%
“…Inactivating mutations in PHF6 were subsequently identified in human leukemia of the T and myeloid lineages, highlighting its role as a tumor suppressor gene in these malignancies (Van Vlierberghe et al 2010, 2011. Our group recently described a tumor-promoting role for Phf6 in a murine model of BCR-ABL1 + B-ALL (Williams et al 2006;Meacham et al 2015). In this study, we found that hairpin-mediated knockdown of Phf6 leads to impaired growth of B-ALL cells in vivo.…”
mentioning
confidence: 54%
“…This is signifi cantly different from the currently used model systems, mainly cancer cell lines (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), and might provide novel insights into mechanisms of tumor maintenance.…”
Section: Discussionmentioning
confidence: 78%
“…Unfortunately, however, this information is available for only a fraction of the mutated cancer genes. Loss-of-function experiments targeting multiple genes were extensively used to investigate tumor vulnerabilities in vivo , using either cancer cell lines or genetically engineered tumors which, however, do not refl ect the genetic diversity of human malignancies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…This effect is reminiscent of RUNX1 mutations in myelodysplastic syndrome, which reduce rRNA synthesis and ribosomal biogenesis, tune down p53 levels, and render hematopoietic stem cells more resilient to stress-induced apoptosis (56). Interestingly, the PHF6 protein, which, like FGF13, interacts with UBF and represses rRNA synthesis (55), is overexpressed in B-cell lymphoma and has been suggested to play a role in progression of this malignancy (57), often driven by c-Myc hyperactivation.…”
Section: Fgf13 Depletion Augments Nucleolar Size and Increases Rrna Andmentioning
confidence: 99%